DEVELOPMENT OF THE SURABAYA BLAURAN TRADITIONAL MARKET MODEL BASED ON THE VALUABLE, RARE, INIMITABLE, ORGANIZED (VRIO) CONCEPT TO INCREASE COMPETITIVE ADVANTAGE IN THE MODERN COMPETITION ERA - M. Azizul Khakim (SEAN Institute, 2023)
This study aims to finalize concepts that can be applied to traditional markets to increase their competitive advantage in the era of modern competition. The research object taken was the Blauran traditional market in Surabaya, because based on observations the researcher found the fact that basically most of the traders in the Blauran market had indirectly applied the VRIO concept and had a special strategy to survive the competition with modernization and advances in science and technology. One of the reasons for this research is to provide dedication in formulating a strategy that can become a reference for traditional markets, MSMEs and the general public who need it..